Performance Evaluation of Public Elementary School Supervisors in Mataram City During Covid-19 - Asiandrayani Asiandrayani; Sukardi Sukardi; Sudirman Wilian (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2021)
The Covid-19 pandemic is the world's first and foremost health crisis. Many states decided to close schools, colleges, and universities. The purpose of this study is to evaluate the performance of state elementary school supervisors in Mataram City with CIPP model that is seen from the aspects of context, input, process, and product. The type of research used by researchers is a descriptive evaluation with quantitative methods. The evaluation model used is CIPP evaluation model. The population in this study is all supervisors of state elementary schools in Mataram City which numbered 34 supervisors. Because the population of this study is less than 100 people, the entire population is used as a sample of 34 supervisors. The results showed that from the context, input, and supervisory process of state elementary schools in Mataram City has done well to produce a good product as well, namely better teacher performance.